ENHANCEMENT OF EFFICIENCY OF WHITE HEAD CABBAGE POLLINATION IN CASE OF LOW POLLEN VIABILITY - D. V. Shumilina; A. I. Batmanova; N. A. Shmykova; L. L. Bondareva (Овощи России, 2015)
The way of improvement of the efficiency of white head cabbage pollination in case of low pollen viability is presented. The optimal culture medium with Tris maintaining pH 8$9 for germination of cabbage pollen was determined.  Pollination of style by the suspension of pollen in the optimal culture medium was suggested. This method allows obtaining of seeds of doubled haploid plants with partially sterile pollen.